2022
DOI: 10.3390/cancers14122990
|View full text |Cite
|
Sign up to set email alerts
|

Close Surgical Margins in Oral and Oropharyngeal Cancer: Do They Impact Prognosis?

Abstract: Introduction. Mucosal margins exhibit a mean shrinkage of 30–40% after resection of oral and oropharyngeal cancers, and an adequate in situ surgical margin frequently results in a pathological close margin. However, the impact on prognosis remains unclear. We investigated the impact of a pathological close margin on disease-free survival (DFS) and overall survival (OS). Methods. We retrospectively reviewed the clinicopathological data of 418 patients diagnosed with squamous cell carcinomas of the oral cavity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…19 Multiple investigators have also obtained excellent oncologic local control using much smaller margins, as low as 1-2 mm, in the oropharynx. 20,21 The NCCN guidelines reflect this evolving area of research for appropriate margin size during transoral and robotic approaches for HPV-associated OPC. 22 Our study has several limitations.…”
Section: Resultsmentioning
confidence: 99%
“…19 Multiple investigators have also obtained excellent oncologic local control using much smaller margins, as low as 1-2 mm, in the oropharynx. 20,21 The NCCN guidelines reflect this evolving area of research for appropriate margin size during transoral and robotic approaches for HPV-associated OPC. 22 Our study has several limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Margins were defined as positive or negative; negative and close margins were adequate . Research on adequate margin distance in HPV-OPSCC has shown that close margins (ie, >1 mm to ≤5 mm) have similar disease-free and overall survival rates than those with margins greater than 5 mm . In a prior report from our research group, patients treated with NECTORS with negative margins (n = 52) have been free of disease on follow-up; 2 patients with positive margins developed distant metastases to the lungs (n = 1) and local recurrence and death (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…18 Research on adequate margin distance in HPV-OPSCC has shown that close margins (ie, >1 mm to ≤5 mm) have similar disease-free and overall survival rates than those with margins greater than 5 mm. 32,33 In a prior report from our research group, 18 patients treated with NECTORS with negative margins (n = 52) have been free of disease on follow-up; 2 patients with positive margins developed distant metastases to the lungs (n = 1) and local recurrence and death (n = 1). That study cohort of patients treated with this same NECTORS protocol demonstrated pathologic complete response in the primary site (72%) and neck (56%).…”
Section: Description and Benefits Of Nectorsmentioning
confidence: 98%
“…However, no association was found between dysplasia in the surrounding tissue and time to LRTF, which was more pronounced in patients without ENE. Literature regarding surgical margin distance in SCCHN 4,5,7,16 has mainly been retrospective and focused on outcomes of patients with OC cancer resections, with some debate about what is an adequate surgical resection margin. Retrospective studies by Varvares et al 4 and Lee et al 16 found that patients with less than 5-mm margins had significantly worse survival that those with margins of 5 mm or greater.…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding surgical margin distance in SCCHN 4,5,7,16 has mainly been retrospective and focused on outcomes of patients with OC cancer resections, with some debate about what is an adequate surgical resection margin. Retrospective studies by Varvares et al 4 and Lee et al 16 found that patients with less than 5-mm margins had significantly worse survival that those with margins of 5 mm or greater. Similarly, a meta-analysis by Anderson et al 5 found that there was a significant reduction in absolute risk (21%) for local recurrence of OC cancer when margins of 5 mm or greater were used as the cutoff for clear margins.…”
Section: Discussionmentioning
confidence: 99%